A South African mixed race lip/philtrum guide for diagnosis of fetal alcohol spectrum disorders. (25th February 2015) - Hoyme, H. Eugene; Hoyme, Derek B.; Elliott, Amy J.; Blankenship, Jason; Kalberg, Wendy O.; Buckley, David; Abdul‐Rahman, Omar; Adam, Margaret P.; Robinson, Luther K.; Manning, Melanie; Bezuidenhout, Heidre; Jones, Kenneth L.; et al.
Abstract : The adverse effects of maternal alcohol use during pregnancy represent a spectrum of growth restriction, facial dysmorphology, and neurocognitive challenges in the offspring. The continuum of diagnoses is referred to as fetal alcohol spectrum disorders (FASD). Short palpebral fissures, a smooth philtrum, and a thin vermilion border of the upper lip comprise the three cardinal facial features of FASD. Early attempts to define a smooth philtrum and thin vermilion border of the upper lip were subjective. Astley and colleagues introduced a 5‐point Likert‐scaled lip/philtrum guide based on Caucasian North American subjects as an objective tool for the evaluation of the facial dysmorphology in FASD. This Caucasian guide has been incorporated into all current diagnostic schemes for FASD. However, broad international clinical experience with FASD indicates racial and ethnic differences with respect to the facial morphology. Because of the substantial number of children with FASD in South Africa among the Cape Coloured (mixed race) population in the Western Cape Province, we developed a specific lip/philtrum guide for that population. The guide incorporates a 45‐degree view of the philtrum that enables an enhanced 3‐dimensional evaluation of philtral height not possible with a frontal view alone. The guide has proven to be a more specific and sensitive tool for evaluation of the facial dysmorphology of FASD in the Cape Coloured population than the use of the previous North American Caucasian guide and points to the utility of racial and ethnic‐specific dysmorphology tools in the evaluation of children with suspected FASD. © 2015 Wiley Periodicals, Inc.